Domain Specificity in Relationship History, Social-Information Processing, and Violent Behavior in Early Adulthood - Pettit, Gregory S. (2010)
Using prospective longitudinal data, we tested 5 hypotheses: (a) that the relation between earlier developmental experiences (peer social rejection and victimization in a romantic relationship) and adult violent behavior toward peers and romantic partners is specific to relationship domain; (b) that the relation between social-information processing (SIP) biases and subsequent violence is also specific to relational domain (romantic partner vs. peer); (c) that the relation between developmental experiences and SIP biases is domain specific; (d) that domain-specific SIP mediates the impact of earlier developmental experiences on later violent behavior; and (e) that harsh parenting early in life is a domain-general predictor of SIP and later violent behavior. Harsh parenting was assessed through interviews with parents when their children were age 5 years. Classroom sociometric assessments indexing peer rejection were completed in elementary school, and self-report of victimization by romantic partners was provided at age 18 years. SIP was assessed via interview at age 22 years, and violent behavior was measured via self-and partner report at ages 23 years and 24 years. Structural equation analyses revealed specificity in the relation between developmental experiences and violence and in the prediction to and from SIP in the peer domain, but not in the romantic-relationship domain. The impact of early harsh treatment on violence toward peers was mediated by SIP biases in the peer domain. These findings provide support for domain specificity in the peer domain but for cross-domain generality in the romantic relationship domain in the development of violent behavior in early adulthood.